Rescuing urban regeneration from urban patronage: towards inclusive development in the Voortrekker Road Corridor - Uppink, Lauren Kim (Graduate School of Development Policy and Practice, 2017)
The Voortrekker Road Corridor in Cape Town was recently identified as an Integration Zone according to National Treasury's Integrated City Development Grant (ICDG). Prior to this a number of private and public stakeholders founded the Greater Tygerberg Partnership, in response to the need for a coordinating body to champion inclusive regeneration and local economic development in the corridor and neighbouring northern suburbs. Funded wholly by the City of Cape Town for its first three years of operation, the Partnership had after two years in operation appeared to have made little progress in catalysing interest and tangible investment in the area, even on a micro level. This dissertation utilises the qualitative analysis method of process tracing for the period of 2012-2015 to explore themes of urban governance and conversely urban patronage. It firstly considers whether the apparent stasis is due to the Partnership being subjected to capture by strong private and political elites. Subsequently it examines whether incremental, micro-level governance initiatives and acts of public entrepreneurship, though seemingly small, have the potential to build momentum capable of overcoming such threatening predatory networks, and in so doing redirect the organisation towards achieving substantive inclusive and equitable regeneration.